Unraveling a Thyroid Collision Tumor: A Rare Case of Concurrent Papillary and Follicular Carcinoma - Gargarin Nabalah; Henky Agung Nugroho; Esti Yuniar Anggrimulya (Open Access Indonesian Journal of Medical Reviews, 2025)
Papillary thyroid carcinoma (PTC) represents the most common thyroid malignancy, accounting for 70-80% of cases, while follicular thyroid carcinoma (FTC) constitutes the second most prevalent differentiated thyroid cancer, comprising 10-15% of thyroid malignancies. The concurrent occurrence of PTC and FTC within the same thyroid gland, known as a collision tumor, is a rare phenomenon, posing diagnostic and therapeutic challenges. This case report aims to describe a unique presentation of this rare entity and discuss its clinicopathological features. We present the case of a 61-year-old female with a history of left thyroidectomy 25 years prior, who presented to our surgical oncology department with a palpable right breast mass. The initial workup revealed metastatic papillary thyroid carcinoma in the breast. Subsequent evaluation of the thyroid bed, including neck ultrasound and fine needle aspiration biopsy (FNAB) of a right thyroid nodule, led to the suspicion of a thyroid malignancy. The patient underwent completion thyroidectomy and central neck dissection. Final histopathological examination of the surgical specimen confirmed the rare diagnosis of a collision tumor, revealing the simultaneous presence of both PTC and FTC within the right thyroid lobe remnant. Immunohistochemical staining further characterized the distinct tumor components. The patient received postoperative radioactive iodine (RAI) ablation and thyroid hormone suppressive therapy. In conclusion, this case underscores the importance of considering the possibility of thyroid collision tumors in patients with thyroid nodules, especially in those with a history of thyroid disease or presentations of metastatic disease from an unknown primary. A comprehensive diagnostic approach, integrating clinical findings, radiological imaging, cytological examination, and detailed histopathological analysis with immunohistochemistry, is crucial for accurate diagnosis.